Barriers to integrating direct oral anticoagulants into anticoagulation clinic care: A mixed‐methods study. Issue 1 (19th October 2018) - Barnes, Geoffrey D.; Acosta, Jennifer; Graves, Christopher; Puroll, Eric; Kline‐Rogers, Eva; Gu, Xiaokui; Townsend, Kevin; McMahon, Ellen; Craig, Terri; Froehlich, James B.
Abstract: Background: Outpatient anticoagulation clinics were initially developed to care for patients taking vitamin K antagonists such as warfarin. There has not been a systematic evaluation of the barriers and facilitators to integrating direct oral anticoagulant (DOAC) care into outpatient anticoagulation clinics. Methods: We performed a mixed methods study consisting of an online survey of anticoagulation clinic providers and semi‐structured interviews with anticoagulation clinic leaders and managers between March and May of 2017. Interviews were transcribed and coded, exploring for themes around barriers and facilitators to DOAC care within anticoagulation clinics. Survey questions pertaining to the specific themes identified in the interviews were analyzed using summary statistics. Results: Survey responses were collected from 159 unique anticoagulation clinics and 20 semi‐structured interviews were conducted. Three primary barriers to DOAC care in the anticoagulation clinic were described by the interviewees: (a) a lack of provider awareness for ongoing monitoring and services provided by the anticoagulation clinic; (b) financial challenges to providing care to DOAC patients in an anticoagulation clinic model; and (c) clinical knowledge versus scope of care by the anticoagulation staff. These themes linked to three key areas of variation, including: (a) the size and hospital affiliation of the anticoagulation clinic; (b) the use of face‐to‐face versus telephone‐based care; and (c) the use of nurses or pharmacists in the anticoagulation clinic. Conclusions: Anticoagulation clinics in the United States experience important barriers to integrating DOAC care. These barriers vary based on the clinic size, model for warfarin care, and staff credentials (nursing or pharmacy).